Friction Stir Welding on AA5083 Tee Joint in 1F Position - Ismail, A. (Springer, 2020)
Friction stir welding (FSW) is a recent technique that exploits a non-consumable rotating welding tool to generate frictional heat and plastic deformation at the welding location. The principal advantages of FSW, being a solid-state process, are low distortion, absence of melt-related defects and high joint strength, even in those alloys that are considered non-weldable by conventional techniques. Hard materials such as steel and other important engineering alloys can now be welded efficiently using this process. The understanding has been useful in reducing defects and improving uniformity of weld properties and expanding the applicability of FSW to new engineering alloys. This project focuses mainly on the experimental study of FSW on AA5083 T-joint in 1F position. This study investigates the jig fixture and tool pin design with effects of pin rotation speed on the macrostructure of the joint. The present work deals with an experimental campaign aiming on FSW on aluminium alloy 5083 T-joint. Tool pins are fabricated using material high tensile steel H13 with angle shoulder with heat treatment process for surface-hardened tools. Â© 2020, Springer Nature Singapore Pte Ltd.